The Disjunction Effect in Choice under Uncertainty - Tversky, Amos; Shafir, Eldar (Psychological Science, 1992)
One of the basic axioms of the rational theory of decision under uncertainty is Savage's (1954) sure-thing principle (STP) It states that if prospect x is preferred to y knowing that Event A occurred, and if x is preferred to y knowing that A did not occur, then x should be preferred to y even when it is not known whether A occurred We present examples in which the decision maker has good reasons for accepting x if A occurs, and different reasons for accepting x if A does not occur Not knowing whether or not A occurs, however, the decision maker may lack a clear reason for accepting x and may opt for another option We suggest that, in the presence of uncertainty, people are often reluctant to think through the implications of each outcome and, as a result, may violate STP This interpretation is supported by the observation that STP is satisfied when people are made aware of their preferences given each outcome